Pembrolizumab-associated anti-MDA5 dermatomyositis in a patient with lung cancer: a first case report - Antonino Marcello Pilia; Lorenzo Salvati; Alessia Guidolin; Francesca Mazzoni; Lorenzo Antonuzzo; Paola Parronchi; Francesco Liotta (Swiss Medical Weekly, 2024)
We report the first case of anti-melanoma differentiation-associated gene 5 (MDA5)-positive dermatomyositis as a systemic immune-related adverse event in a 64-year-old man receiving pembrolizumab to treat advanced lung cancer. The patient experienced hypothyroidism, myalgia, skin involvement, dyspnoea and diarrhoea. Laboratory tests revealed raised inflammatory markers, hypercreatinekinasemia and anti-MDA5 autoantibodies. Electroneuromyography and pathognomonic signs on physical examination confirmed the diagnosis of pauci-myopathic dermatomyositis. Pembrolizumab was discontinued and immunosuppressive therapy led to rapid and progressive improvement, with complete remission of dermatomyositis. This case report widens the spectrum of systemic immune-related adverse events associated with pembrolizumab.